Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/978-94-017-9032-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigation of Carotenoids Involved in Non-Photochemical Fluorescence Quenching

Abstract: SummaryThis chapter will review the recent results in the fi eld of carotenoid photophysics and relate excited-state properties of carotenoids to their potential roles in the dissipation of the singletexcited state of chlorophyll a resulting in non-photochemical quenching (NPQ) of chlorophyll fl uorescence. Investigations into the structure and dynamics of excited states of carotenoids have revealed potential mechanisms regarding the involvement of spectroscopically Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…A large body of mechanistic work ranging from carotenoids dissolved in various solvents to isolated pigment-binding complexes, isolated organelles, and mutants/transgenic organisms with altered carotenoid composition, has revealed multiple potential functions for carotenoids. A given carotenoid can apparently have different multiple functions depending on its specific microenvironment because "energetics and dynamics of carotenoid excited states" are controlled not only by factors such as conjugated-chain length and functional groups but also by, "perhaps most importantly, carotenoid interaction with the local environment" [19]. Furthermore, how much carotenoid is accumulated, and its location, is affected by an organism's genetic makeup as well as its acclimation to the external environment in which it developed.…”
Section: Carotenoids In a Nutshellmentioning
confidence: 99%
“…A large body of mechanistic work ranging from carotenoids dissolved in various solvents to isolated pigment-binding complexes, isolated organelles, and mutants/transgenic organisms with altered carotenoid composition, has revealed multiple potential functions for carotenoids. A given carotenoid can apparently have different multiple functions depending on its specific microenvironment because "energetics and dynamics of carotenoid excited states" are controlled not only by factors such as conjugated-chain length and functional groups but also by, "perhaps most importantly, carotenoid interaction with the local environment" [19]. Furthermore, how much carotenoid is accumulated, and its location, is affected by an organism's genetic makeup as well as its acclimation to the external environment in which it developed.…”
Section: Carotenoids In a Nutshellmentioning
confidence: 99%
“…The photophysical mechanism of how excitation energy is removed from excited chlorophyll was under debate for decades (see edited volume by Demmig-Adams et al [ 52 ]) after the initial proposal of a link between zeaxanthin and the dissipation of excitation energy as heat [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Polivka and Frank [ 60 ] elaborated on the difficulties of studying these mechanisms due to the impact of the microenvironment on the photophysical properties of photosynthetic pigments. Since then, Graham Fleming’s group conducted fluorescence lifetime studies in vivo in an intact photosynthetic organism and concluded that zeaxanthin was involved in both of the two different photophysical mechanisms (energy transfer and charge transfer) capable of de-exciting chlorophyll thermally [ 61 , 62 ].…”
Section: Xanthophyll Cycle Conversion State and Dissipation Of Unumentioning
confidence: 99%
“…twisting) and the local environment (e.g. polarity of the medium) (Polívka and Sundström 2004; Polívka and Frank 2016). The S0–S2 transition of the different carotenoids is strongly allowed and visible as the three-peak absorption in the 400–500 nm range in solution.…”
Section: Discussionmentioning
confidence: 99%
“…The S0–S2 transition of the different carotenoids is strongly allowed and visible as the three-peak absorption in the 400–500 nm range in solution. In vivo, protein-bound carotenoids show a red-shift in the absorption spectrum due to the dispersion interactions of the carotenoid with the protein (Polívka and Frank 2016). Due to this absorbance shift, the chemical conversion of the VAZ carotenoids in vivo is observed as an absorbance change in the 500–570 nm region with maximum around 531 nm (Gamon et al 1990; Peñuelas et al 1995).…”
Section: Discussionmentioning
confidence: 99%